Pengaruh Green Accounting dan Carbon Emission Disclosure terhadap Tax Avoidance pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2025 - Azisah, Andi Nurul; Surianto, Nurul Maghfirah (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines the effect of green accounting and carbon emission disclosure on tax avoidance in energy companies listed on the Indonesia Stock Exchange during 2021–2025. This study uses a quantitative approach with secondary data obtained from annual reports, financial statements, and sustainability reports. The sample was selected using purposive sampling, resulting in 10 companies and 50 firm-year observations. Tax avoidance is proxied by the effective tax rate (ETR), while green accounting and carbon emission disclosure are measured using disclosure indices. The data were analyzed using panel data regression with the random effect model. The results show that green accounting and carbon emission disclosure do not significantly affect ETR. These findings indicate that broader environmental and carbon disclosure does not necessarily reflect lower tax avoidance. This study highlights the importance of evaluating corporate sustainability comprehensively by considering environmental disclosure and fiscal accountability.